Caracterização das condições de acessibilidade previstas para o acadêmico com necessidades educacionais especiais nas Instituições públicas de Ensino Superior do Estado do Paraná - Castilho, Annamaria Coelho de (2012)
With the creation of Program University for All (PROUNI) in 2004 and the approval of Program Inclusion in 2005, actions around the inclusion of students with Special Educational Needs (NEE) in Higher Education were intensified, and the subject has become found more frequently in national academic production, space majorly occupied by research dedicated to the other levels of education. In public Higher Education Institutions (IES), were then, structured Accessibility Centers with the goal to enable actions to admission and permanence of students that present those needs. These actions refer to architectural, communicational, and methodological accessibility, as well as other support strategies, such as, tutoring. In this study we aim to characterize the accessibility strategies for the permanence of students with NEE in Federal and State Public Universities in the State of Paraná, foreseen in the documentation of nuclei/programs of accessibility of these institutions. The text organizes itself the following way: in the first part is held a theoretical review that encompasses brief explanation of the history of Special Education, definitions, history of Higher Education and accessibility in this modality; ultimately, conceptualization of the theoretical reference that bases out analysis is crafted. Methodologically, it is descriptive research, with documental analysis; based on the theoretical reference of Behavior Analysis, field of knowledge based on the philosophy of Radical Behaviorism by B. F. Skinner (2003). A functional analysis of the documents of the Accessibility Centers was performed, articulating what they offer with federal law and detailing more specifically: the population served, the forms of accessibility contemplated and utilized strategies. Four categories of accessibility were listed in view of literature and documents analyzed: architectural, communicational, attitudinal and methodological-pedagogical. As a result, we find that the legal texts and documents of public content bring descriptions of the behavior of nuclei, only two IES explained the discriminative stimulus or context for the occurrence of actions. All documents include forms of accessibility: architectural, communication, methodological-pedagogical. The attitudinal accessibility, more complex to be studied, was contemplated directly by the resolutions of two of the institutions surveyed. The public IES of Paraná are in accordance with the Federal Law on accessibility in higher education, but the resolutions of Accessibility Programs are vague as to the conditions that properly provides for the academic with NEE. This implies what is expected is to be taken as advice or suggestion, not a requirement, something that is the right of the student. An inclusive perspective in education refers to the implementation and diversification of education practices that strengthen and alter the quality of education, what results in the acquisition of an enriched repertoire to meet the demands of the contemporary society by all individuals. A culture with diverse practices that contemplates the well being and learning of all promotes its maintenance and development. We emphasize that we analyze the proposals within documents such as and resolutions and information from the Centers websites, however we are unable to ascertain whether what is written in these materials in fact occurs, it is needed more research in this direction.